Is There More Than One Road to Nevus-Associated Melanoma? - Roberta Vezzoni; Claudio Conforti; Silvia Vichi; Roberta Giuffrida; Chiara Retrosi; Giovanni Magaton-Rizzi; Nicola di Meo; Maria Antonietta Pizzichetta; Iris Zalaudek (Mattioli1885, 2020)
The association of melanoma with a preexisting nevus is still a debated subject. Histopathological data support an associated nevus in approximately 30% of all excised melanomas. The annual risk of an individual melanocytic nevus becoming malignant is extremely low and has been estimated to be approximately 0.0005% (or less than 1 in 200,000) before the age of 40 years, to 0.003% (1 in 33,000) in patients older than 60 years. Current understanding, based on the noticeable, small, truly congenital nevi and nevi acquired early in life, is that the first develops before puberty, presents with a dermoscopic globular pattern, and persists for the lifetime, becoming later a dermal nevus in the adult. In contrast, acquired melanocytic nevi develop mostly at puberty and usually undergo spontaneous involution after the fifth decade of life. The purpose of this review is to analyze the data of the literature and to propose, on the basis of epidemiological and clinical-dermoscopic characteristics, a new model of melanogenesis of nevus-associated melanoma.